Empowering Student’s Creativity Through Pixton Integrated Project Based Learning in Elementary School - Mashfufah, Aynin; Utama, Candra; Untari, Esti; Sari, Novia Siska Puspita; Hidayatulloh, Moh. Alif (UIN Siber Syekh Nurjati Cirebon, 2024)
AbstractThe characteristics of students, especially elementary school student, are familiar with the use of gadgets and even digital applications. In addition, the integration of technology in learning is currently not uncommon as a result of the covid-19 pandemic. This research aims to empower students' creativity through project-based learning by integrating the Pixton application. The method used is pre-experimental with a single-subject design. The research sample involved 28 elementary school grade V students and was grouped into 7 groups. The data collection method uses a creativity assessment rubric with four creativity indicators. The data is analyzed in a quantitative descriptive manner and presented in the form of graphs to see trends across all indicators of creativity. The results of the study show that students' creativity collaboratively develops very well in the aspect of generating digital comic story ideas according to the topic of bullying. The implication of this study is that digital application-assisted learning provides an opportunity to provide engaging learning for students and real experiences.Keywords: project-based learning, creativity, pixton, digital comic.AbstrakKarakteristik peserta didik khususnya siswa sekolah dasar, sudah tidak asing lagi dengan penggunaan gawai bahkan aplikasi digital. Selain itu, integrasi teknologi dalam pembelajaran saat ini bukanlah hal asing akibat dari pandemi covid-19. Penelitian ini bertujuan untuk memberdayakan kreativitas peserta didik melalui pembelajaran berbasis proyek dengan mengintegrasikan aplikasi Pixton. Metode yang digunakan adalah pra-eksperimen dengan desain subjek tunggal. Sampel penelitian melibatkan 28 siswa kelas V sekolah dasar dan dikelompokkan menjadi 7 kelompok. Metode pengumpulan data menggunakan rubrik penilaian kreativitas dengan empat indikator kreativitas. Data dianalisis secara deskriptif kuantitatif dan disajikan ke dalam bentuk grafik untuk melihat kecenderungan pada seluruh indikator kreativitas. Hasil penelitian menunjukkan bahwa kreativitas siswa secara kolaboratif berkembang sangat baik pada aspek menghasilkan ide cerita komik digital sesuai dengan topik perundungan. Implikasi dari penelitian ini adalah pembelajaran berbantuan aplikasi digital memberikan kesempatan untuk memberikan pembelajaran yang menarik bagi siswa dan pengalaman nyata.Kata kunci: pembelajaran berbasis proyek, kreativitas, pixton, komik digital.